the ELECTROSPINNING-ASSISTED FABRICATION OF ZNO NANOSTRUCTURES: OPTIMIZATION OF PARAMETERS FOR TAILORED PARTICLE SIZE - Aizhan Rakhmanova (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
The present study focuses on the synthesis of ZnO nanostructures via an electrospinning-assisted technique, followed by calcination under carefully controlled thermal conditions. The electrospinning process resulted in the formation of continuous, uniform, and bead-free polymeric precursor fibers, with a noticeable reduction in average fiber diameter. This clearly demonstrates the influence of electrospinning parameters, such as applied voltage, solution concentration, and flow rate, on the resulting fiber morphology. Subsequent calcination not only removed the polymeric matrix but also induced the crystallization of ZnO, transforming the fibrous structure into well-defined nanoparticles. The crystallite size of the obtained ZnO was strongly dependent on the calcination temperature, with the smallest crystallites achieved under optimized thermal treatment, thereby offering a route to fine-tune the nanostructure dimensions. Elemental analysis by energy-dispersive X-ray spectroscopy (EDS) confirmed the exclusive presence of zinc and oxygen, verifying the high purity and compositional integrity of the synthesized material. Furthermore, X-ray diffraction (XRD) analysis revealed sharp and intense diffraction peaks corresponding solely to the hexagonal wurtzite phase of ZnO, with no evidence of secondary phases or impurities. These results collectively demonstrate that electrospinning, coupled with controlled calcination, provides a robust, cost-effective, and scalable approach for producing high-quality ZnO nanostructures with desirable structural and compositional features. Such nanostructures hold significant promise for diverse applications, including gas sensing.